Pemanfaatan Bubuk Bawang Merah Brebes untuk Meningkatkan Durabilitas Mi Basah - Rahmawati, Yuniarti; Purwanti, Yunika; Masrikhiyah, Rifatu (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Wet noodles are a highly perishable food product due to their high water content (32–35%). The use of synthetic preservatives can negatively impact health. One potential alternative to synthetic pre-servatives is Brebes shallots (Allium cepa L.), which are rich in phenolic compounds. This study aimed to evaluate the effectiveness of Brebes shallot powder as a natural preservative for wet noodles. The research used an experimental method with a completely randomized design (CRD), where wet noodles were enriched with varying proportions of shallot powder (0, 5, 10, 15, 20, and 25%). Analyses were performed on shelf life, physical parameters (elasticity and water absorption), chemical properties (proximate and phenolic content), and sensory attributes. The results showed that the 25% shallot powder treatment achieved the longest shelf life, lasting 67.33 hours—five times longer than the control group (without preservatives), which lasted only 15.33 hours. The measured total phenolic content increased from 0.51 to 2.08%. In terms of sensory attributes, the use of shallot powder significantly affected the taste, aroma, color, and texture of the wet noodles, although elasticity decreased as the proportion of shallot powder increased.